The Consequences of Glacier Retreat Are Uneven Between Plant Species - Losapio, Gianalberto; Cerabolini, Bruno E. L.; Maffioletti, Chiara; Tampucci, Duccio; Gobbi, Mauro; Caccianiga, Marco (Frontiers in Ecology and Evolution, 2021)
Glaciers are retreating worldwide, exposing new terrain to colonization by plants. Recently-deglaciated terrains have been a subject of ecological studies for a long time, as they represent a unique natural model system for examining the effects of global warming associated with glacier retreat on plant species and the spatio-temporal dynamic of plant communities. However, we still have a limited understanding of how physical and biotic factors interactively influence species persistence and community dynamics after glacier retreat and glacier extinction. Using hierarchical joint species distribution models, we integrated data on species occurrence at fine spatial scale, spatio-temporal context, environmental conditions, leaf traits and species-to-species associations in plant communities spanning 0 to ca 5,000 years on average after glacier retreat. Our results show that plant diversity initially increases with glacier retreat, but ultimately decreases after glacier extinction. The 22% of plant species nonlinearly respond to glacier retreat and will locally disappear with glacier extinction. At the local scale, soil carbon enrichment and reduction of physical (topographic) disturbance positively contribute to distribution patterns in 66% of the species, indicating a strong signal of environmental filtering. Furthermore, positive and negative associations among species play a relevant role (up to 34% of variance) in driving the spatio-temporal dynamic of plant communities. Global warming prompts a shift from facilitation to competition: positive associations prevail among pioneer species, whereas negative associations are relatively more common among late species. This pattern suggests a role of facilitation for enhancing plant diversity in recently-deglaciated terrains and of competition for decreasing species persistence in late stages. In summary, although plant diversity initially increases with glacier retreat, more than a fourth of plant species are substantially declining and will disappear with glacier extinction. Leveraging community survey data and hierarchical models is valuable for forecasting biodiversity change and mitigating cascading effects of glacier retreat on mountain ecosystems.